Fabrication of an Ionomer-Free Electrode Containing Vertically Aligned One-Dimensional Nanostructures for Alkaline Membrane Fuel Cells. Issue 11 (15th November 2021) - Kim, Sungjun; Choi, Jiwoo; Sung, Yung-Eun; Choi, Mansoo; Jang, Segeun
Abstract : An ionomer-free electrode containing vertically aligned one-dimensional nanostructures was designed and fabricated for anion exchange membrane fuel cells (AEMFCs) by hydrothermal and vapor deposition processes. The silver-coated zinc oxide (ZnO) nanorod arrays (diameter = ca. 100 nm) were directly aligned with the gas diffusion layer (GDL), and these one-dimensional structures of the electrode enhanced the mass transport of the reactants to the catalytic surface via its short diffusion pathway and ionomer-free nature. Applied as a cathode, the membrane electrode assembly (MEA) containing the vertically aligned gas diffusion electrode showed about 80% increased maximum power density than that of MEA containing a conventional electrode, which consisted of randomly dispersed carbon-supported nanoparticle catalysts and an ionomer. Moreover, the durability test revealed that the prepared ionomer-free catalyst layer was a more stable electrode than the conventional one. Also, water consumption and oxygen transport characteristics of AEMFC with the ionomer-free electrode at the cathode were intensively investigated by varying the electrode thickness and compositions.